trans–cis S-Benzyl dithiocarbazate - Shanmuga Sundara Raj, S.; Yamin, Bohari M.; Yussof, Yusrabbil A.; Tarafder, M. T. H.; Fun, Hoong-Kun; Grouse, K. A. (International Union of Crystallography (IUCr), 2000)
In the crystal structure of the title compound, C8H10N2S2, the molecules are linked by N—H...S hydrogen bonds between the imino group and the thione-S atoms to form a chain along the b axis. The dithiocarbazate moiety is rotated by 85.8 (2)° with respect to the phenyl ring.